Constraints on Transport of Injured Victims after the Earthquake for Disaster Victims’ Evacuation Model Development: A Phenomenological Study - Muhammad, Muhammad; Kamil, Hajjul; Adlim, Muhammad; Irwandi, Irwandi (Heca Journal of Applied Sciences, 2024)
The big earthquake has an impact on the risk of injury to the victims. The wounded victim needed urgent medical assistance to survive. The effectiveness of this service depends heavily on the response speed of stakeholders. To increase the response rate, a detailed emergency response plan is needed. The study aims to identify restrictive factors in evacuating victims of post-earthquake injuries. This qualitative research has a phenomenological design. Participants in this study were 15 nurses who participated in the Disaster Victim Evacuation (DVE) process and who met the criteria with the purposive sampling technique. Data is collected through a deep interview (IDI) using open questions. Data analysis is done using the inductive content analysis method. Two themes contributed to the DVE process as an ERP, namely, 1) restriction of institutional support and 2) cancellation of evacuation routes. These findings have provided an overview of several factors that directly contributed to the implementation of the DVE process.